Case report: SARS-CoV-2 specific T-cells are associated with myocarditis after COVID-19 vaccination with mRNA-1273 - Stervbo, Ulrik; Van Bracht, Marc; Philippou, Stathis; Babel, Nina; Westhoff, Timm H. (Frontiers in Medicine, 2023)
Vaccination of SARS-CoV-2 with BNT162b2 or mRNA-1273 both have a low incidence of induction of myocarditis. Here we report on utilizing adaptive immune receptor repertoire sequencing (AIRR-Seq) as a way to assess the specificity of tissue infiltrating immune cells.